Development of Madura Tourism-Based Children's Encyclopedia To Foster Tourism Literacy of Elementary School Students - Mardiyana, Isna Ida; Pritasari, Ade Cyntia (UIN Sunan Kalijaga Yogyakarta, 2024)
The introduction of tourism potential for students, especially elementary school students, is necessary to foster tourism literacy. The study aims to produce and describe the eligibility of developing a Madura Tourism-Based Encyclopedia to increase tourism literacy for elementary school students that is valid, effective, and interesting. The method used in this study is a model 4-D, which consists of four phases, namely the definition, design, development, and dissemination. However, this study only deals with the development stage. Data was collected through validation questionnaires, student response questionnaires, and learning outcomes tests after using the Madura Tourism-Based Encyclopedia. The results of the study show that: (1) the average percentage validation of the Madura tourism-based Encyclopedia from validators is 90.5% with very valid criteria; (2) The results of the class trial were to the aspect of the student response questionnaire to the Madura Tourism-Based Encyclopedia obtaining a score of 85,38% with exciting criteria. (3) The results of the field class trial on the aspect of the student comprehension test show that the percentage of student learning completeness is 93,33 %, which indicates that the Madura Tourism-Based Encyclopedia can be said to be effective.